1992
DOI: 10.1159/000177696
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Deficiency and Iron Absorption in Adult Gambian Men

Abstract: Iron absorption from 3.38 mg 58Fe was measured in riboflavin-deficient Gambian men with haemoglobin (Hb) less than 11.5 g/dl before and after oral riboflavin therapy, and the results compared with a group not receiving riboflavin. Riboflavin status (as determined by erythrocyte glutathione reductase activation coefficient) and Hb increased in the riboflavin-supplemented but not placebo group. Plasma ferritin levels were low and did not change in either group. There was very wide variation in percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…with a placebo (35). In lactating Guatemalan women, we found that adding riboflavin to iron supplements improved plasma ferritin marginally more than did iron supplementation alone, although hemoglobin concentrations were not increased after 2 mo of supplementation with iron, riboflavin, or both (LH Allen, MT Ruel, JE Casterline, and LM Rogers, unpublished observations, 2000).…”
Section: Figurementioning
confidence: 82%
“…with a placebo (35). In lactating Guatemalan women, we found that adding riboflavin to iron supplements improved plasma ferritin marginally more than did iron supplementation alone, although hemoglobin concentrations were not increased after 2 mo of supplementation with iron, riboflavin, or both (LH Allen, MT Ruel, JE Casterline, and LM Rogers, unpublished observations, 2000).…”
Section: Figurementioning
confidence: 82%
“…Diabetes risk (718) ; insulin secretion (157,786) ; blood pressure (787) ; CVD (788 -790) ; cardiac arrhythmias (791) ; kidney health (792) and stones (793) ; bone health (794) ; hypercalciura (795) Thiamin (vitamin B 1 ) (204,796,797) : Antioxidant (798) ; glucose metabolism and Krebs cycle (799) ; mental and neuronal health (800) Riboflavin (vitamin B 2 ) (204,796) : Haematopoiesis (801,802) ; gastrointestinal development (803) ; mental health (804) ; vision (805) ; cardiovascular protection (806,807) ; cancer (808,809) Niacin (vitamin B 3 ) (204,796) :…”
Section: Appendixmentioning
confidence: 99%
“…In one clinical study, ribo¯avin supplementation produced a three-fold increase in erythrocyte B 6 conversion, followed by a rise in a-and b-globin chain synthesis 96 . Another possibility suggested by animal studies is that ribo¯avin affects iron absorption by maintaining the absorptive capacity of gastrointestinal villi, but studies among humans have not yet observed measurable change in iron absorption following ribo¯avin supplementation 97,98 . Table 6 summarizes ribo¯avin supplementation trials that have assessed effects on anaemia.…”
Section: Ribo¯avinmentioning
confidence: 99%